Developing Student’s Worksheet on Two-Dimensional Figures Based on Ethnomathematics For V Grade of Elementary School - Nyamik Rahayu Sesanti; Dyah Triwahyuningtyas; Fitria Anggitasari (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
The purpose of this study is to describe the process, validity, practicality, and effectiveness of Student Worksheets (LKPD) on two-dimensional figures based on Ethnomathematics. This study employed the ADDIE development model with five stages, namely: Analysis, Design, Development, Implementation, and Evaluation. The subject of the trial was the fifth graders of elementary school. Data collection instruments used were validation assessment questionnaires for content experts, linguists, media experts, and practitioners (teachers), and the documentation. The data analysis technique employed descriptive qualitative and quantitative. The results of the study indicated that the Student Worksheet is feasible with a percentage acquisition of 90.9%; in terms of practicality, the acquisition of a percentage was 96.4% and 93%; in terms of effectiveness, the acquisition of an average value was 80. Based on the results of the study, the Student Worksheet (LKPD) on two-dimensional figures based on Ethnomathematics can be used in learning because it meets the criteria of feasible, practical, and effective. Thus, Student Worksheet (LKPD) on two-dimensional figures based on Ethnomathematics can be useful and make it easier for the fifth graders of Elementary School to learn Mathematics that contains cultural information and can be used as a teacher's reference in developing instructional materials especially Student Worksheet.